1980
DOI: 10.1128/aac.18.5.675
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative correlation between penicillin resistance and beta-lactamase activity specified by the R plasmids R1, R1 bla-45, and RP1 in Escherichia coli K-12

Abstract: A mutant of the R plasmid Rl which synthesizes a f,-lactamase with altered kinetic characteristics was isolated. The level of penicillin resistance specified by this plasmid was correctly predicted from the properties of the wild-type Rl according to a simple theoretical model published by Zimmermann and Rosselet (Antimicrob. Agents Chemother. 12:368-372, 1977). The model also accounts for the high level of penicillin resistance specified by the R plasmid RP1.A theoretical model which attempts quantitatively t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The suggestion that some 3-lactamase-specifying plasmids also determine a barrier that hinders the diffusion of drugs across the outer layers of the cell was proposed to explain the expression of highlevel carbenicillin resistance in strains with low or undetectable enzyme activity (82,437). Recently it was shown that the resistance expressed by plasmids with defective ,B-lactamases was entirely attributable to residual P-lactamase activity of the mutant proteins (76,77).…”
Section: Inactivation Mechanismsmentioning
confidence: 99%
“…The suggestion that some 3-lactamase-specifying plasmids also determine a barrier that hinders the diffusion of drugs across the outer layers of the cell was proposed to explain the expression of highlevel carbenicillin resistance in strains with low or undetectable enzyme activity (82,437). Recently it was shown that the resistance expressed by plasmids with defective ,B-lactamases was entirely attributable to residual P-lactamase activity of the mutant proteins (76,77).…”
Section: Inactivation Mechanismsmentioning
confidence: 99%
“…This conclusion is drawn from a comparison of the properties of pUB251, pUB252, and RP1: the former two plasmids are derivatives of Rl whose penicillin resistance phenotypes are indistinguishable from that of RP1 (Table 4). Further support is provided by the model presented in the accompanying paper (6), in which the differences in penicillin resistance mediated by Rl and RP1 are quantitatively accounted for solely in terms of the properties of the R-factor f,-lactamase.…”
Section: Discussionmentioning
confidence: 99%
“…The properties of pUB254, an Rl derivative able to confer higher levels of penicillin resistance than Rl, but with less than 10% of the enzyme activity (Table 4), support the idea that mutants of the type IIIa (TEM) ,8-lactamase can arise in which enzymes of low specific activity confer relatively high levels of penicillin resistance. (A quantitative analysis of the relationship between penicillin resistance and the properties of the R plasmid /3-lactamase is described in the accompanying paper [6]). An intermediate situation is also possible, in which both bla and irp contribute to the penicillin resistance phenotype of RP1 amp-i.…”
Section: Discussionmentioning
confidence: 99%
“…Rms325 and RP4 conferred a 10to 20fold-higher degree of ,B-lactamase activity than did Rms212 and Rl. The type I 1-lactamases specified by these R plasmids have been purified and have been shown to have identical specific activities, that is, 4.10 x 104 and 6.38 x 104 molecules of substrate hydrolyzed per min per molecule of enzyme at 30°C with benzylpenicillin and ampicillin as a substrate, respectively (6,12; unpublished data of T. Sawai et al). Therefore, the variation of the levels of the ,B-lactamase activity per host cell could be ascribed to the production of an equivalent number of the enzyme molecules.…”
Section: Cloning Of Each -Lactamase Gene Specified Bymentioning
confidence: 99%
“…At present it seems that type Ia and type Ib correspond to TEM-1 and TEM-2, respectively. On the basis of previous studies, it could be assumed that R plasmids included in the lower-level-group specify type Ia enzyme, and R plasmids in the higherlevel group specify type lb enzyme, when the absolute levels of 1-lactamase activity are compared among R plasmids under stringently controlled conditions (6,12). To elucidate the variation in f-lactamase activities in cells carrying these R plasmids from the standpoint of the bla gene expression, the bla genes on four kinds of R plasmid were cloned, and the levels of ,Blactamase production and the rates of transcription from the bla gene were examined in the present paper.…”
Section: Cloning Of Each -Lactamase Gene Specified Bymentioning
confidence: 99%